Self-Sufficient Class VII Cytochromes P450: From Full-Length Structure to Synthetic Biology Applications. Issue 11 (November 2021) - Correddu, Danilo; Di Nardo, Giovanna; Gilardi, Gianfranco
Abstract : Members of class VII cytochromes P450 are catalytically self-sufficient enzymes containing a phthalate dioxygenase reductase-like domain fused to the P450 catalytic domain. Among these, CYP116B46 is the first enzyme for which the 3D structure of the whole polypeptide chain has been solved, shedding light on the interaction between its domains, which is crucial for catalysis. Most of these enzymes have been isolated from extremophiles or detoxifying bacteria that can carry out regio- and enantioselective oxidation of compounds of biotechnological interest. Protein engineering has generated mutants that can perform challenging organic reactions such as the anti-Markovnikov alkene oxidation. This potential, combined with the detailed 3D structure, forms the basis for further directed evolution studies aimed at widening their biotechnological exploitation. Highlights: The self-sufficient nature of some bacterial cytochromes P450 makes them attractive biocatalysts as they do not require a redox partner protein for catalysis. The self-sufficient class VII is the first full length multidomain P450 for which the 3D structure has been solved. Many self-sufficient P450s are present in extremophiles in polluted sites, suggesting a high stability in extreme conditions, which is an advantage for biocatalysts and bioremediation purposes. Protein engineering has successfully targeted self-sufficient P450s: the reductase domain can supply electrons to other enzymes in chimeric fusion proteins, whereas the P450 domain can be designed for high activity and selectivity. Semi-rational and random mutagenesis have created variants with improved catalytic efficiency towards substrates of biotechnological interest that are converted in high value chemicals.